2022
DOI: 10.1093/brain/awac396
|View full text |Cite
|
Sign up to set email alerts
|

Altered synaptic connectivity in anin vitrohuman model of STXBP1 encephalopathy

Abstract: Early infantile developmental and epileptic encephalopathies are devastating conditions, generally of genetic origin, but the pathological mechanisms often remain obscure. A major obstacle in this field of research is the difficulty of studying cortical brain development in humans, at the relevant time period in utero. To address this, we established an in vitro assay to study the impact of gene variants on the developing human brain, using living organotypic cultures of the human subplate and neighbouring cor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 31 publications
(45 reference statements)
1
14
0
Order By: Relevance
“…We also recently showed that oligomeric tau derived from brains of individuals with Progressive Supranuclear Palsy (PSP) can be taken up into synapses, and induced gliosis in HBSCs 63 . Other studies have established HBSCs as an excellent tool to investigate: physiological properties of human neurons 12,60,61,[106][107][108][109][110][111][112] , tumour environments [113][114][115] , neurodegenerative disease 98,99,[116][117][118][119][120][121][122] , epileptic activity 123,124 and developmental disorders 125 . By correlating responses to treatments, as well as changes in endogenous dynamics, to patient age, sex, brain region, genetics and lifestyle risk factors, we propose that HBSCs represent an extremely powerful tool for both discovery and translational research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also recently showed that oligomeric tau derived from brains of individuals with Progressive Supranuclear Palsy (PSP) can be taken up into synapses, and induced gliosis in HBSCs 63 . Other studies have established HBSCs as an excellent tool to investigate: physiological properties of human neurons 12,60,61,[106][107][108][109][110][111][112] , tumour environments [113][114][115] , neurodegenerative disease 98,99,[116][117][118][119][120][121][122] , epileptic activity 123,124 and developmental disorders 125 . By correlating responses to treatments, as well as changes in endogenous dynamics, to patient age, sex, brain region, genetics and lifestyle risk factors, we propose that HBSCs represent an extremely powerful tool for both discovery and translational research.…”
Section: Discussionmentioning
confidence: 99%
“…Dissection and culture methods to generate human brain slice cultures (HBSCs) were adapted from published studies 60,106,[126][127][128] B9001), 1 ug/ml laminin (APExBIO: A1023), 1X penicillin/streptomycin (ThermoFisher: 15140122), 3 units/ ml nystatin (Merck: N1638) and 20 mM HEPES. For all samples, the time taken from surgical tissue removal to slices being plated in Wash Solution 2 was kept to a minimum (< 2 hours).…”
Section: Generation and Maintenance Of Human Brain Slice Cultures (Hb...mentioning
confidence: 99%
“…For instance, traditional ex vivo methods such as organotypic cultures have been exploited as a valid system to investigate human neurodevelopmental alterations of specific networks. Indeed, organotypic brain slice cultures represent a physiological threedimensional model of the brain that can be interrogated to define the impact of genetic and environmental insults and pathophysiological responses (Onorati et al, 2016;Grønning Hansen et al, 2020;McLeod et al, 2022). This method, indeed, allows the culture of neural complex tissue preserving the architecture and cell interactions, even if the obtainment and longterm maintenance of the culture may be challenging.…”
Section: Shifting Borders-exploring Cortico-thalamic Development Thro...mentioning
confidence: 99%
“…For longer term use, including the application of viral vectors, human brain slices can be maintained in organotypic culture 109,110 . This approach has been extended recently to the study of the developing human brain 111 . Resected human slices do suffer some disadvantages.…”
Section: Translational Capabilities Of In Vitro Preparationsmentioning
confidence: 99%
“…109,110 This approach has been extended recently to the study of the developing human brain. 111 Resected human slices do suffer some disadvantages. Patient donors and tissue samples are highly heterogeneous with key variables including patient age, sex, ASM history as well as the anatomic location of the seizure-onset zone and the viability of the resected tissue.…”
Section: Improved Translation Of In Vitro Models-use Of Human-based P...mentioning
confidence: 99%